OIL REVENUE AND POVERTY IN NIGERIA: THE SOUTH-SOUTH PERSPECTIVE IN POST COVID-19 ERA - CHIJIOKE, MERCY IHUOMA; OLISAH, REMIGIUS CHINEDU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2023)
Oil revenue has remained the live wire of Nigeria’s economy given that it contributes over 80 per cent to the nation’s foreign exchange earnings and more than 50 per cent to her gross domestic product. Thus, Nigeria rely heavily on oil revenue in funding her annual budget. The oil is naturally located within the South-South region of the country, by implication, the region contributes significantly to Nigeria’s revenue, yet, it is characterized by high rate of poverty. Using a descriptive approach and data obtained from the World Bank and National Bureau of Statistics among others, the study revealed an independent relationship between oil revenue and the rate of poverty in the region. This is because, the region still had high poverty rate even in the years of oil boom, hence, COVID-19 pandemic which led to drastic fall in oil revenue thereafter cannot be held responsible for growing poverty rate in the region. Consequently, the study suggests that since in both times of high and low revenue generation from oil including the present post COVID-19 era, the south-south region has remained in poverty, there is need for stakeholders to refocus on other resources beside oil. In other words, they should concentrate on human capital development as well as technological innovations. This will improve the competitiveness of businesses in the region, attract investors, create employment opportunities and reduce the rate of poverty, hence improve standard of living in the southsouth region.